Systemic Mesenchymal Stromal Cell Transplantation Prevents Functional Bone Loss in a Mouse Model of Age-Related Osteoporosis - Kiernan, Jeffrey (Stem Cells Transl Med, 2016)
Age-related osteoporosis is driven by defects in the tissue-resident mesenchymal stromal cells (MSCs), a heterogeneous population of musculoskeletal progenitors that includes skeletal stem cells. MSC decline leads to reduced bone formation, causing loss of bone volume and the breakdown of bony microarchitecture crucial to trabecular strength. Furthermore, the low-turnover state precipitated by MSC loss leads to low-quality bone that is unable to perform remodeling-mediated maintenance—replacing old damaged bone with new healthy tissue. Using minimally expanded exogenous MSCs injected systemically into a mouse model of human age-related osteoporosis, we show long-term engraftment and markedly increased bone formation. This led to improved bone quality and turnover and, importantly, sustained microarchitectural competence. These data establish proof of concept that MSC transplantation may be used to prevent or treat human age-related osteoporosis. SIGNIFICANCE: This study shows that a single dose of minimally expanded mesenchymal stromal cells (MSCs) injected systemically into a mouse model of human age-related osteoporosis display long-term engraftment and prevent the decline in bone formation, bone quality, and microarchitectural competence. This work adds to a growing body of evidence suggesting that the decline of MSCs associated with age-related osteoporosis is a major transformative event in the progression of the disease. Furthermore, it establishes proof of concept that MSC transplantation may be a viable therapeutic strategy to treat or prevent human age-related osteoporosis.